INTEGRATING ISLAMIC CRIMINAL LAW INTO INDONESIA’S NEW CRIMINAL CODE: A STUDY OF LEGAL PLURALISM AND NORMATIVE TRANSFORMATION - Junaidi Abdillah; Tri Nurhayati; Maulana Anwar (Faculty of Law, Universitas Diponegoro, 2026)
The enactment of New Criminal Code signifies a pivotal shift in Indonesia's criminal law, aiming to harmonize national identity with religious, customary, and Western legal principles. This study investigates the influences of Islamic law to the New Criminal Code, focusing on criminal acts. Understanding this interaction is essential to explain how Islamic legal principles contribute to shaping contemporary national criminal law reform in Indonesia. This study employs doctrinal legal research, which examines legal principles, statutory provisions, and legal doctrines related to Islamic criminal law and Indonesia’s New Criminal Code. The research relies primarily on legal documents, including legislation, scholarly literature, and authoritative legal texts. The collected data were analyzed qualitatively using the analytical model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. The research identifies two key findings: (1) Islamic law significantly influences the provisions of the New Criminal Code, evident in material and formal legality aligning with societal values; and (2) Islamic principles exhibit greater responsiveness in addressing legality standards, the retroactive principle, and crime classification. These findings underscore the progressive and integrative potential of Islamic law in enriching national criminal law reforms. This study offers a novel contribution by mapping the substantive transformation of Islamic criminal law principles into Indonesia’s New Criminal Code, thereby highlighting the role of Islamic legal thought in contemporary national criminal law reform.